Study on Pressure Characteristics of Disturbed Wells due to Interwell Fracturing Interference and Its Application in Small Well Spacing Fracturing - Yanjun Zhang; Fan Lu; Zhibo Guo; Le Yan; Tianlu Xu; Hongkui Ge; Shun Liu; Desheng Zhou (Geofluids)
In order to maximize the production of unconventional oil and gas reservoirs, the well spacing has been shrinking continuously. Thus, the interwell fracturing interference usually occurs, which brings some problems affecting the fracturing efficiency. As one of the most challenging issues, a set of efficient methods for diagnosing wellhead pressure characteristics of interwell fracturing interference need to be established. In this study, taking the shale oil well platform of Lucaogou Formation as an example, the wellhead pressure resulted from interwell fracturing interference was analyzed. A real-time diagnosis method for each fractured stage based on the power-law model was proposed; the interference was further classified into four types. Meanwhile, the parameters of well spacing and completion were optimized. The results show that the power-law model of nonuniform pressure transmission in complex fracture networks is applicable for the evaluation of wellhead pressure fluctuation in real time. According to the differential pressure, the differential pressure derivative and the variation range of pressure interference during fracturing (PIF) and the interwell fracturing interference of Lucaogou Formation shale oil can be classified into pressure communication type (I), hydraulic fractures connected type (II), large natural fractures interconnected type (III), and composite type (IV). Specifically, the type of III and IV will do harm to the production, while the type of I is conducive to supplementing formation energy. The type of II may be conducive to supplementing formation energy in some situations. The well spacing of shale oil in the Lucaogou Formation is preferably 150~200 m, and the injection rate is optimized to 12 m3/min. The findings of this study can help for better understanding of identifying wellhead pressure characteristics of interwell fracturing interference and optimizing well spacing and completion parameters.